Exploration of Education on Doctor-patient Communication Skills in Clinical Internship Teaching of Orthokeratology Lens Fitting - Zhao, Bingxin; Yang, Xiaodi; Lv, Yong; Wang, Weiqun (Journal of Educational Research and Policies, 2025)
Effective doctor-patient communication stands as a fundamental competency for healthcare professionals and a prerequisite for successful clinical practice. Within orthokeratology lens fitting procedures, exemplary communication skills coupled with appropriate humanistic care not only significantly enhance patient cooperation but also improve adherence to treatment protocols, thereby ensuring safer and more effective orthokeratology application. The purpose of this study is to explore how to effectively cultivate the communication skills of interns during clinical internship teaching in the fitting process of orthokeratology lenses, and to propose corresponding strategies for the current situation of internship teaching. Through the integration of theoretical frameworks and practical applications, we present a series of evidence-based pedagogical strategies designed to advance trainees’ communication proficiency in orthokeratology fitting, ultimately optimizing patient care delivery.